Novel colorimetric chemosensors containing pyridine moiety for detection of some cations in water and crops samples: Design, synthesis, and evaluation - Ayman M. Algohary; Mohamed M. Hassan; Maher A. El-Hashash; Sameh A. Rizk; Manahil B. Elamin; Amani H. Ahmed (Journal of Saudi Chemical Society)
This investigation deals with synthesis of some novel chemo sensors for identifying cations in drinking water and agricultural crops. This takes place via interaction of 2,5-dioxo-1,2,3,4-tertrahydropyridine-3-carbonitrile (3) and 2-thioxo-5-oxo-1,2,3,4-tertrahydropyridine-3-carbonitrile (4) with CuII and CoII. The novel compounds' structures have been examined using spectrum data (IR, 1H NMR, 13C NMR, and MS) as well as elemental and physical studies. Complexation behaviors of Compounds 3 and 4 as organic ligands were predicted, discussed, and calculated via Density-Functional Theory (DFT) and Colorimetric investigation. The newly synthesized receptors 3 and 4 showed selective colormetric sensing capability for some cations by color shifting from colorless to pale violet in a nearby ideal aqueous solution enabling naked eye identification and quantitative determination of cooper (CuII) and cobalt (CoII) metal ion.